Osteoarthropathy In Mucopolysaccharidosis Type II - Nascu, Ioana; Grigorescu-Sido, Paula; Al-Khzouz, Camelia; Bucerzan, Simona; Denes, Carmencita; Lazea, Cecilia (Medicine and Pharmacy Reports, 2014)
Introduction. Mucopolysaccharidosis type II (MPS type II, Hunter syndrome) is a rare ( 1/1500.000), X-linked inherited disorder (affects boys) due to deficiency of the lysosomal enzyme iduronate sulfatase (Xq.28). The complex clinical picture includes osteoarthropathy with a tendency to flexion stiffness and disability. In our country, the specific diagnosis and enzyme replacement therapy (ERT), are recently available in the Center for Genetic Pathology Cluj. Objectives. Assessment of clinical features, radiological and imaging of osteoarthropathy in MPS type II and their evolution under ERT. Material and methods. The study included 9 male patients with a suggestive clinical picture of MPS type II; the diagnosis was confirmed by enzymatic assay and the patients were treated with ERT. Osteoarthropathy was assessed before treatment: a) clinical tests (joint goniometry, walking test) and b) radiology (X-rays of the hand and wrist, spine and pelvis), bone densitometry in five patients. Clinical tests were repeated after therapy. Results. Chronic osteoarthropathy was present in all patients. Joint mobility was reduced with quasi stationary trend after 12 months of treatment. The walking test was improved after treatment. Radiological assessment revealed: hand bones changes, delayed bone age, vertebral changes, pelvis changes, kipho-scoliosis and aseptic necrosis of the femoral head in 100%, 88%, 88%, 55% and 11% respectively. Bone mineral density was normal in five of the nine patients evaluated. Conclusions. Chronic osteoarthropathy with flexion stiffness is an essential component of the clinical picture of MPS type II. ERT allows an improvement/arrest of evolution (depending on disease severity and time of initiating therapy).